Media Influence on Women's Beauty, Psychology and Social Perceptions: A Longitudinal Study - Junaidi (Journal Discrimination and Injustice, 2025)
This study examines the influence of mass media and digital media on women's beauty, psychological, and social perceptions in the context of local communities in Mesuji Regency, Lampung Province. Through a three-year longitudinal study, this study aims to understand the dynamics of changes in women's beauty perceptions along with media exposure and how these narratives influence women's self-image construction, social interactions, and psychological well-being. A longitudinal study was chosen to capture the shift in personal values ​​and experiences in depth and continuously. This study uses a qualitative method with a social construction theory and media representation approach, and is analyzed through a mubadalah perspective that emphasizes the principles of gender reciprocity and justice. Data were obtained through in-depth interviews, observations of social media activities, and documentation of local media content. The results show that mass media still dominates homogeneous beauty narratives, while digital media provides space for more diverse representations but still creates social pressure on appearance. These findings emphasize the importance of media literacy and women's active involvement in content production to build inclusive, fair, and liberating beauty standards from the dominance of hegemonic body images